Effect of Different Flower Composts on the Growth of Yard Long Bean (Vigna unguiculata subsp. sesquipedalis) - Ahmed, Md Sabbir; Ahammed, Md Shafin; Billah, Shaikh Motasim (South Asian Journal of Agriculture, 2025)
The experiment was conducted in the Soil, Water and Environment Discipline, Khulna University, Bangladesh, from May to October 2022 to assess the effect of different flower composts on the growth of yard long bean (Vigna unguiculata subsp. sesquipedalis). The experiment was arranged in complete randomized design (CRD) with three replications. The experiment included seven treatments: (1) Control, (2) Marigold flower compost at 1000 Kg ha-1, (3) Marigold flower compost at 2000 Kg ha-1, (4) Rose flower compost at 1000 Kg ha-1, (5) Rose flower compost at 2000 Kg ha-1, (6) Chrysanthemum flower compost at 1000 Kg ha-1 (7) Chrysanthemum flower compost at 2000 Kg ha-1. Plant morphological and physiological attributes were measured in the experiment. The study found that the addition of marigold flower compost to the soil at a rate of 2000 Kg ha-1 had a beneficial impact on the leaf count on yard long bean. The order of increase was as T2>T4>T1>T3>T6>T5>T0. The root length was significantly influenced by different treatments. The root length per plant observation was as T2>T1>T4>T5>T6>T3>T0. There was no significant difference between the treatments T3, T4, T5, and T6. The application of marigold flower compost at a rate of 2000 Kg ha-1 showed significant enhancement of shoot length than other treatments. Thus, the shoot length per plant observation was as T2>T1>T4>T3>T6>T2>T5. The fresh weight per plant was as T2>T4>T3>T1>T5>T6>T0. The application of marigold flower compost at 2000 Kg ha-1 also showed higher positive effects than other treatments. The fresh weight per plant (g) observation was as T2>T4>T3>T1>T5>T6>T0. Marigold flower compost at 2000 Kg ha-1 showed a positive impact on the basis of the dry weight per plant. Moisture content per plant varied insignificantly compared to the control and other treatments. The highest moisture content (87.15%) was found in control treatment and the lowest moisture content was recorded (85.13%) in T4. Therefore, moisture content (%) observation was as T0>T6>T1>T3>T2>T5>T4. The findings of this study suggest that the incorporation of marigold flower compost in soil at 2000 kg ha-1 has a potentially positive effect on the growth of yard long bean (Vigna unguiculata subsp. sesquipedalis). South Asian J. Agric. Vol. 11, No. 2, Dec., 2025: 37-45